Considerations to set up a manufacturing plant for producing a nutritional supplement for children - Godefroy, Lorena (2019)
Child malnutrition is a current problem in Peru. This research aims to demonstrate the social, technical and economic feasibility of manufacturing a nutritional product for children, and using part of the profits to support a social program to reduce chronic child malnutrition in the country’s provinces. To this end, industrial engineering tools were used to calculate the market demand, the technical specifications of the product, the size and design of the manufacturing plant, the economic andfinancial analysis, and the social impact.